The relative effects of input and output based instruction on the development of L2 knowledge and the relationships with individual differences in working memory - Yan Liang; Lawrence Jun Zhang (Asian-Pacific Journal of Second and Foreign Language Education)
Abstract While the relative effects of Processing instruction (PI) and various types of output-based instruction have been widely examined, the types of L2 knowledge generated after receiving instruction are under-researched. Moreover, the relationships between learners’ individual differences and the comparative effects of PI and output-based instruction have not yet been investigated. This study examined the types of L2 knowledge generated after three instructional methods and the relationships with individual differences in working memory capacity. A total of 86 adult beginning-level L2 Chinese learners were assigned into three experimental groups—processing instruction (PI), meaning-based output instruction (MOI), combined instruction (CI)—and a control group. An Untimed Grammaticality Judgment Test (UGJT) and an oral Elicited Imitation Test (EIT) were used to measure learners’ development of explicit and implicit knowledge respectively. A counting span task was employed to assess learners’ working memory capacity. The results demonstrated that the three types of instructional treatments brought about equal gains on the measure of explicit knowledge, and the meaning-based output instruction group made more gains on the measure of implicit knowledge. Working memory was negatively correlated with the UGJT for the MOI group. The results suggest that the three instructional treatments may aid the development of both explicit and implicit knowledge and the MOI group may have an advantage in facilitating the development of L2 implicit knowledge. The findings also suggest that learners with lower working memory capacity may benefit more from the MOI.